Maritime Transportation Network Analysis and Development Strategy in the Maluku Archipelago: An Island Cluster Typology Approach - Yuni Andriyani Safitri; Wijayanto Suat; Luthfi Muta'ali; Andri Kurniawan; Vrita Tri Aryuni; Syarifuddin Adjam; Anggit Sasmita (Universitas Lambung Mangkurat, 2026)
Ambon City depends on commodity supplies from surrounding regions, including foodstuffs from Seram and Buru Islands and fishery products from Tual, reflecting economic specialization across Maluku's island clusters that creates interdependence and necessitates inter-regional interaction. This study aims to: (1) analyze the maritime transportation network system between island clusters, (2) analyze socio-economic interaction potential, and (3) formulate a maritime transportation network development strategy in the Maluku Archipelago. A mixed-method approach was employed, covering 12 island clusters with 12 ports serving as service centers. Data were collected through in-depth interviews with maritime transportation stakeholders, field observations, and document studies. Connectivity was analyzed using König and Shimbel indices, while accessibility was assessed based on Black's (1991) scheme. The gravity model measured interaction strength between island clusters, and the scalogram method determined service center hierarchies. SWOT analysis integrated with a typology matrix was used for strategy formulation. Results indicate: (1) that connectivity and accessibility remain generally low, with 50% classified as moderate, and only Island Cluster VII (Ambon and Lease Islands) exhibiting high accessibility. (2) Interaction patterns are concentrated in Cluster VII as the center of government and growth, with the highest interaction occurring between Cluster VII and Cluster II (Piru). (3) Based on island cluster typology, development strategies are differentiated into four categories: ST (Strength-Threat) for clusters with low access and interaction; WT (Weakness-Threat) for low access-moderate interaction; WO (Weakness-Opportunity) for moderate access-low interaction; and SO (Strength-Opportunity) for clusters with high access and interaction such as Cluster VII. The formulated strategies focus on improving port infrastructure quality and quantity as well as developing human resources in the maritime transportation sector to support regional mobility and economic growth.